Relationship Between Teacher Professional Competences and Teacher Work-Autonomy - Fachrurrazi, Fachrurrazi (Yayasan Sukma, 2017)
The article discusses the relationship between teacher professional competences and teacher work-autonomy at Sukma Bangsa Schools in Aceh, Indonesia. The study investigated differences in teacher professional competences and teacher work-autonomy in terms of gender, school location, classroom teacher/subject teacher, grade level and teaching experiences. The study indicated that most teachers of Sekolah Sukma Bangsa in Aceh were at moderate degree of teacher professional competences and most of the teachers attained a moderate degree of work-autonomy. The study showed that when the level of teacher work-autonomy increased, the level of teacher professional competences escalated; while lower level of teacher autonomy was associated with lower level of teacher professional competences. Furthermore, the study revealed that a degree to which teachers perceived work-autonomy and a degree to which teachers perceived professional competences were diverse based on gender, classroom/subject teacher, experience, level of school and location of school, even though the differences were not statistically significant. [Artikel ini mendiskusikan hubungan antara kompetensi professional guru dan otonomi-kerja guru. Tujuan dari riset ini adalah untuk menginvestigasi hubungan antara kompetensi professional guru dan otonomi-kerja guru, serta perbedaan kompetensi professional guru dan perbedaan otonomi kerja guru berdasarkan gender, lokasi sekolah, guru kelas/guru pelajaran, level kelas atau pengalaman mengajar. Hasil riset juga mengindikasi bahwa ada korelasi yang positif dan moderat antara otonomi-kerja guru dan kompetensi profesional guru. Hasil riset mengindikasi bahwa ketika level otonomi-kerja guru meningkat, level kompetensi profesional guru juga naik, dan rendahnya tingkatan otonomi-kerja guru dihubungkan dengan rendahnya kompetensi professional guru. Hasil riset juga mengindikasikan level otonomi-kerja dan level kompetensi professional guru bervariasi berdasarkan gender, lokasi sekolah, guru kelas/guru pelajaran, level kelas dan pengalaman mengajar, walaupun perbedaannya tidak signifikan secara statistik.]